Steel slag lightweight aggregate and preparation method thereof
The stability of steel slag is improved through carbonization reaction and the preparation of steel slag light aggregates is solved, and the problem of poor stability of steel slag is achieved efficiently using steel slag resources and CO2 fixation is achieved to produce high-strength ultra-high performance concrete.
Patent Information
- Application Number
- CN202510028765.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
The early hydration of steel slag is not high, the stability is poor, and it is difficult to effectively utilize steel slag resources.
Through the carbonization reaction, MgO and f-CaO are converted into MgCO3 and calcium carbonate to improve the volume stability of steel slag, and a light aggregate of steel slag, including steel slag powder, porous silicate powder, silicate cement, silicate fume and water, and improve its performance through granulation and carbonization curing treatment.
It significantly improves the volume stability and CO2 fixation capacity of steel slag, improves waste utilization efficiency, reduces carbon emissions, and can produce ultra-high performance concrete with strength grades up to 120MPa or above.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a steel slag lightweight aggregate and a preparation method thereof. Background Art
[0003] Developing a circular economy with clean production as the center and achieving sustainable development are the inevitable choices for the steel industry. Attaching importance to the recovery and utilization of steel slag has put forward a more scientific development concept for the resource utilization technology of steel slag in the steel industry. How to reasonably utilize steel slag is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present invention provides a steel slag lightweight aggregate and a preparation method thereof. Aiming at the problems of low early hydration degree and poor stability of steel slag, the present invention converts 58.83% of MgO in the RO phase into MgCO3 and about 85% of f-CaO into calcium carbonate through carbonization reaction, which can effectively improve the volume stability of steel slag.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention proposes a steel slag lightweight aggregate, comprising the following raw materials in parts by weight: 35-60 parts of steel slag powder, 15-30 parts of porous silicate powder, 8-12 parts of silicate cement, 1-5 parts of silica fume, and 15-25 parts of water.
[0007] Preferably, the steel slag powder comprises the following components in mass fractions:
[0008] CaO: 52.62% ~ 58.23%, SiO2: 29.71% ~ 36.85%, Al2O3: 2.57% ~ 5.94%, MgO: 3.47% ~ 6.68%, loss on ignition 1.72% ~ 3.16%;
[0009] The steel slag powder has a particle size of 0.05 to 0.15 mm.
[0010] Preferably, the porous silicate powder is diatomaceous earth powder, and the mass content of SiO2 in the diatomaceous earth powder is greater than or equal to 88.95%; the average pore size of the diatomaceous earth powder is 56-57nm, the particle size is ≤0.075mm, and the loss on ignition is 0.35-0.45%.
[0011] Preferably, the silicate cement is silicate cement with a strength grade of 52.5.
[0012] Preferably, the specific surface area of the silica fume is 24 to 26 m 2 / g, loss on ignition ≤5.0%.
[0013] In a second aspect, the present invention further provides a method for preparing the steel slag lightweight aggregate, comprising the following steps:
[0014] S1, modifying the porous silicate powder with a modifier, and crushing the modified porous silicate powder to obtain a modified porous silicate powder;
[0015] S2, mixing steel slag powder, modified porous silicate powder, silicate cement and silica fume to obtain a mixture;
[0016] S3, adding water to the mixture, granulating, and obtaining light aggregate;
[0017] S4. Put the light aggregate into a carbonizing kettle for carbonation curing, and then perform standard curing to obtain carbonized steel slag light aggregate.
[0018] Preferably, after mixing the modifier and the porous silicate powder, water is added and the mixture is continuously mixed to obtain a mixture;
[0019] The mixture is placed in a calcining furnace and heated from room temperature to 800-1100°C within 3-4 hours, and kept warm for 1.5-2 hours. The modified mixture is then crushed to a particle size of ≤0.075 mm to obtain modified porous silicate powder.
[0020] Preferably, the modifier is Na2CO3, and the mass of the modifier is 5-10% of the mass of the porous silicate powder. After mixing the modifier and the porous silicate powder, in the step of adding water, the mass of the water is 0-15% of the mass of the porous silicate powder.
[0021] Preferably, during granulation, the granulation angle of the granulator is 40 to 60° and the rotation speed is 30 to 40 r / min;
[0022] The particle size of light aggregate is 0.1~4.75mm.
[0023] Preferably, the process parameters of carbonation curing control are: carbonization temperature is 20-24°C, relative humidity is 50%-70%, carbonization carbon dioxide pressure is 0.1-0.5MPa, and carbonization time is 4-48h;
[0024] The process parameters for standard curing control are: curing temperature of 18-22°C, relative humidity greater than or equal to 95%, and curing time of 28 days.
[0025] The steel slag lightweight aggregate and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0026] The steel slag light aggregate of the present invention can not only efficiently absorb solid waste steel slag, but also effectively absorb and fix CO2. The present invention is applied to the construction industry to improve the efficiency of waste utilization, and its waste utilization rate can reach more than 40%, and the effective carbon fixation is 50% to 60%, which significantly reduces carbon emissions; the steel slag light aggregate prepared by the present invention can be applied to large-volume concrete projects, effectively reducing the utilization rate of sand and gravel, and protecting the ecological environment. At the same time, the light aggregate prepared by the present invention has a cylinder pressure strength of more than 18MPa and an apparent density of 1550 to 1850kg / m 3 , water absorption rate of 10% to 15%, with fine interconnected pores with pore size of 0.01 to 100 nm, and the interconnected pores account for more than 50% of the total porosity, showing good internal curing effect. When used in concrete, ultra-high performance concrete with a strength grade of more than 120 MPa can be prepared, and the volume stability is strong. It has excellent practical value. The carbonized steel slag light aggregate prepared by the present invention can be used as a light aggregate to partially or completely replace sand and gravel to produce ultra-high performance concrete, with a strength grade of more than 120 MPa, effectively reducing the utilization rate of sand and gravel, protecting the ecological environment, and can also be used as aggregate to produce building concrete, self-repairing concrete, road concrete, etc. Large-scale consumption of carbonized steel slag can, on the one hand, improve the activity of steel slag and solve the problem of poor stability, and on the other hand, it can consume CO2, providing a new way for the comprehensive utilization of steel slag, and also providing a new idea for carbon emission reduction in the building materials industry. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0029] The embodiment of the present application provides a steel slag lightweight aggregate, comprising the following raw materials in parts by weight: 35 to 60 parts of steel slag powder, 15 to 30 parts of porous silicate powder, 8 to 12 parts of silicate cement, 1 to 5 parts of silica fume, and 15 to 25 parts of water.
[0030] The steel slag light aggregate of the present invention has calcium silicate as the main mineral component in the steel slag, which can react with CO2 to form a carbonation reaction, and the carbonization reaction activities of f-CaO, f-MgO and Ca(OH)2 in the steel slag are relatively high, and the carbonization degree is also relatively high. The carbonation reaction of steel slag can effectively improve the utilization rate of steel slag, and at the same time achieve the effect of carbon fixation. The carbonized steel slag light aggregate of the present invention can not only efficiently absorb solid waste steel slag, but also effectively absorb and fix CO2. The application of the present invention in the construction industry can improve the efficiency of waste utilization, and the waste utilization rate can reach more than 40%, and the effective carbon fixation is 50% to 60%, which significantly reduces carbon emissions.
[0031] In some embodiments, the steel slag powder used is converter steel slag from Beihai City, Guangxi Zhuang Autonomous Region, and the steel slag powder includes the following components by mass fraction:
[0032] CaO: 52.62% ~ 58.23%, SiO2: 29.71% ~ 36.85%, Al2O3: 2.57% ~ 5.94%, MgO: 3.47% ~ 6.68%, loss on ignition 1.72% ~ 3.16%;
[0033] The particle size of the steel slag powder is 0.05 to 0.15 mm.
[0034] Since the particle size of steel slag has a great correlation with the degree of carbonation reaction, steel slag needs to be ball-milled and sieved to obtain fine powder before use. The carbonization degree of steel slag with a particle size of ≤0.075mm can reach more than 85%.
[0035] In some embodiments, the porous silicate powder is diatomaceous earth powder from Linjiang City, Jilin Province, and the mass content of SiO2 in the diatomaceous earth powder is greater than or equal to 88.95%; the average pore size of the diatomaceous earth powder is 56-57nm, the particle size is ≤0.075mm, the loss on ignition is 0.35-0.45%, the adsorption performance is strong, and the bulk density is light.
[0036] In some embodiments, the silicate cement is a commercially available silicate cement with a strength grade of 52.5.
[0037] In some embodiments, the silica fume used is a commercially available material, and the specific surface area of the silica fume is 24 to 26 m 2 / g, loss on ignition ≤5.0%, water requirement ≤3%.
[0038] Based on the same inventive concept, the present invention also provides a method for preparing steel slag lightweight aggregate, comprising the following steps:
[0039] S1, modifying the porous silicate powder with a modifier, and crushing the modified porous silicate powder to obtain a modified porous silicate powder;
[0040] S2, mixing steel slag powder, modified porous silicate powder, silicate cement and silica fume to obtain a mixture;
[0041] S3, adding water to the mixture, granulating, and obtaining light aggregate;
[0042] S4. Put the light aggregate into a carbonizing kettle for carbonation curing, and then perform standard curing to obtain carbonized steel slag light aggregate.
[0043] In some embodiments, after mixing the modifier with the porous silicate powder, water is added and the mixture is continuously mixed to obtain a mixture;
[0044] The mixture is placed in a calcining furnace and heated from room temperature (25° C.) to 800-1100° C. within 3-4 hours, and kept warm for 1.5-2 hours. The modified mixture is then crushed to a particle size of ≤0.075 mm to obtain modified porous silicate powder.
[0045] In some embodiments, since the particle size of steel slag has a great correlation with the degree of carbonation reaction, the steel slag needs to be ball-milled and sieved to obtain fine powder before use. The carbonization degree of steel slag with a particle size of ≤0.075 mm can reach more than 85%.
[0046] In some embodiments, the modifier is Na2CO3, and the mass of the modifier is 5-10% of the mass of the porous silicate powder. After mixing the modifier with the porous silicate powder, in the step of adding water, the mass of the water is 0-15% of the mass of the porous silicate powder.
[0047] In some embodiments, during granulation, the granulator has a granulation inclination angle of 40 to 60° and a rotation speed of 30 to 40 r / min;
[0048] The particle size of light aggregate is 0.1~4.75mm.
[0049] Specifically, in some embodiments, steel slag powder, modified porous silicate powder, silicate cement, and silica fume are mixed to obtain a mixture; the mixture is first poured into a granulator and dry-mixed for 10 seconds, and then water is added to the mixture, and granulation is continued to obtain a light aggregate with a particle size of 0.1 to 4.75 mm.
[0050] In some embodiments, the process parameters of carbonation curing control are: carbonization temperature of 20-24° C., relative humidity of 50%-70%, carbonization carbon dioxide pressure of 0.1-0.5 MPa, and carbonization time of 4-48 hours.
[0051] Specifically, the granulated light aggregate is first placed in an oven, and then placed in a carbonization kettle. After exhausting the air in the carbonization kettle, 0.1-0.5MPa of CO2 is introduced for a carbonization time of 4-48h to carry out a carbonization enhancement reaction. The completely carbonized light aggregate needs to be placed in a standard curing room for standard curing until the corresponding age.
[0052] In some embodiments, the process parameters of standard curing control are: curing temperature of 18-22° C., relative humidity greater than or equal to 95%, and curing time of 28 days.
[0053] The steel slag light aggregate prepared by the present invention can be applied to large-volume concrete projects, effectively reducing the utilization rate of sand and gravel and protecting the ecological environment. At the same time, the light aggregate prepared by the present invention has a cylinder pressure strength of more than 18MPa and an apparent density of 1550-1850kg / m 3 , water absorption rate of 10% to 15%, with fine interconnected pores with pore diameters of 0.01 to 100 nm, and the interconnected pores account for more than 50% of the total porosity, showing good internal curing effect. When used in concrete, ultra-high performance concrete with a strength grade of more than 120MPa can be prepared, and the volume stability is strong. It has excellent practical value.
[0054] The steel slag lightweight aggregate and the preparation method thereof of the present invention are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means adopted in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0055] In the following examples and comparative examples, the steel slag powder used is converter steel slag from Beihai City, Guangxi Zhuang Autonomous Region, and the steel slag powder includes the following components by mass fraction: CaO: 56.62%, SiO2: 32.21%, Al2O3: 3.25%, MgO: 5.43%, and loss on ignition 2.49%;
[0056] The average particle size of the steel slag powder is 0.1 mm.
[0057] The porous silicate powder is diatomite powder from Linjiang City, Jilin Province. The SiO2 mass content in the diatomite powder is 88.95%, the average pore diameter is 56.2nm, the particle size is ≤0.075mm, and the ignition loss is 0.39%.
[0058] The silicate cement is commercially available silicate cement with a strength grade of 52.5.
[0059] The silica fume used is commercially available material, and the specific surface area of silica fume is 24m 2 / g, loss on ignition ≤5.0%, water requirement ≤3%.
[0060] Example 1
[0061] The embodiment of the present application provides a steel slag lightweight aggregate, comprising the following raw materials in parts by weight: 39 parts of steel slag powder, 26 parts of porous silicate powder, 10.4 parts of silicate cement, 2.6 parts of silica fume, and 22 parts of water;
[0062] The carbonized steel slag lightweight aggregate and the preparation method thereof comprise the following steps:
[0063] S1, mixing the modifier with 26 parts by weight of porous silicate powder, adding water, and continuing to mix to obtain a mixture;
[0064] The mixture is placed in a calcining furnace and heated from room temperature to 1000°C within 3 hours, and kept at this temperature for 1.5 hours. After the modification is completed, the mixture is crushed to a particle size of ≤0.075 mm to obtain a modified porous silicate powder;
[0065] The modifier is Na2CO3, and the mass of the modifier is 7% of the mass of the porous silicate powder. After the modifier and the porous silicate powder are mixed, in the step of adding water, the mass of the water is 15% of the mass of the porous silicate powder.
[0066] S2, 39 parts by weight of steel slag powder (grind and crush the steel slag powder before use, and sieve to obtain steel slag with a particle size of ≤0.075 mm), the modified porous silicate powder prepared in S1, 10.4 parts by weight of silicate cement, and 2.6 parts by weight of silica fume are mixed to obtain a mixture;
[0067] S3, set the granulator granulation angle to 45°, the speed to 36r / min; pour the mixture in S2 into the granulator, dry mix for 10s, then add 22 parts by weight of water to the mixture, continue granulation, and obtain a light aggregate with an average particle size of 2.5mm;
[0068] S4. Put the light aggregate in S3 into the carbonization kettle, exhaust the air in the carbonization kettle, introduce 0.3MPa CO2, and carbonize and cure for 24h at a temperature of 22℃ and a relative humidity of 60%. Put the completely carbonized light aggregate into the standard curing room for standard curing for 28d;
[0069] The process parameters of standard curing control are: curing temperature is 20°C and relative humidity is 96%.
[0070] Example 2
[0071] The embodiment of the present application provides a steel slag lightweight aggregate, comprising the following raw materials in parts by weight: 48.4 parts of steel slag powder, 20.8 parts of porous silicate powder, 8.3 parts of silicate cement, 2.1 parts of silica fume, and 20.4 parts of water;
[0072] The above-mentioned steel slag lightweight aggregate and preparation method thereof include the following steps:
[0073] S1, mixing the modifier with 20.8 parts by weight of porous silicate powder, adding water, and continuing to mix to obtain a mixture;
[0074] The mixture is placed in a calcining furnace and heated from room temperature to 1000°C within 3 hours, and kept at this temperature for 1.5 hours. After the modification is completed, the mixture is crushed to a particle size of ≤0.075 mm to obtain a modified porous silicate powder;
[0075] The modifier is Na2CO3, and the mass of the modifier is 7% of the mass of the porous silicate powder. After the modifier and the porous silicate powder are mixed, in the step of adding water, the mass of the water is 15% of the mass of the porous silicate powder.
[0076] S2, 48.4 parts by weight of steel slag powder (grind and crush the steel slag powder before use, and sieve to obtain steel slag with a particle size of ≤0.075 mm), the modified porous silicate powder in S1, 8.3 parts by weight of silicate cement, and 2.1 parts by weight of silica fume are mixed to obtain a mixture;
[0077] S3, set the granulator granulation angle to 45° and the rotation speed to 36r / min; pour the mixture in S2 into the granulator, dry mix for 10s, then add 20.4 parts by weight of water to the mixture, continue granulation, and obtain a light aggregate with an average particle size of 2.5mm;
[0078] S4. Put the light aggregate in S3 into the carbonization kettle, exhaust the air in the carbonization kettle, introduce 0.3MPa CO2, and carbonize and cure for 24h at a temperature of 22℃ and a relative humidity of 60%. Put the completely carbonized light aggregate into the standard curing room for standard curing for 28d;
[0079] The process parameters of standard curing control are: curing temperature is 20°C and relative humidity is 96%.
[0080] Example 3
[0081] The embodiment of the present application provides a carbonized steel slag lightweight aggregate, comprising the following raw materials in parts by weight: 56.5 parts of steel slag powder, 14.1 parts of porous silicate powder, 8.5 parts of silicate cement, 2.1 parts of silica fume, and 18.8 parts of water;
[0082] The carbonized steel slag lightweight aggregate and the preparation method thereof comprise the following steps:
[0083] S1, mixing the modifier with 14.1 parts by weight of porous silicate powder, adding water, and continuing to mix to obtain a mixture;
[0084] The mixture is placed in a calcining furnace and heated from room temperature to 1000°C within 3 hours, and kept at this temperature for 1.5 hours. After the modification is completed, the mixture is crushed to a particle size of ≤0.075 mm to obtain a modified porous silicate powder;
[0085] The modifier is Na2CO3, and the mass of the modifier is 7% of the mass of the porous silicate powder. After the modifier and the porous silicate powder are mixed, in the step of adding water, the mass of the water is 15% of the mass of the porous silicate powder.
[0086] S2, 56.5 parts by weight of steel slag powder (grind and crush the steel slag powder before use, and sieve to obtain steel slag with a particle size of ≤0.075 mm), the modified porous silicate powder in S1, 8.5 parts by weight of silicate cement, and 2.1 parts by weight of silica fume are mixed to obtain a mixture;
[0087] S3, set the granulator granulation angle to 45°, the speed to 36r / min; pour the mixture in S2 into the granulator, dry mix for 10s, then add 18.8 parts by weight of water to the mixture, continue granulation, and obtain a light aggregate with an average particle size of 2.5mm;
[0088] S4. Put the light aggregate in S3 into the carbonization kettle, exhaust the air in the carbonization kettle, introduce 0.3MPa CO2, and carbonize and cure for 24h at a temperature of 22℃ and a relative humidity of 60%. Put the completely carbonized light aggregate into the standard curing room for standard curing for 28d;
[0089] The process parameters of standard curing control are: curing temperature is 20°C and relative humidity is 96%.
[0090] Comparative Example 1
[0091] This comparative example provides a fired light aggregate, comprising the following raw materials in parts by weight: 48 parts of shale, 24 parts of fly ash, 6.8 parts of mineral powder, 1.2 parts of silicon carbide, and 20 parts of water;
[0092] The method for preparing the fired lightweight aggregate comprises the following steps:
[0093] S1, 48 parts by weight of shale with a particle size of 3.5 mm crushed by a small jaw crusher are dried (7 hours), ground (48 minutes) and then discharged for standby use;
[0094] S2, the crushed shale in S1, 24 parts by weight of fly ash, and 6.8 parts by weight of mineral powder are mixed in a small ball mill for 10 minutes; after the three raw materials are mixed, 1.2 parts by weight of silicon carbide are added, and the mixture is mixed and stirred with a mortar mixer for 5 minutes to obtain a mixed powder;
[0095] S3, the mixed powder in S2 and 20 parts by weight of water are stirred in a blender for 4 minutes, the plasticized mud ball is taken out, put into a basin and covered with a wet cloth for about 30 minutes, and then rolled into a ball with a diameter of about 10 mm, and the rolled ball is placed in a porcelain plate and dried in a cool place;
[0096] S4, the dried pellets are heated from room temperature to 1140°C within 65 minutes, the roasting time is 10 minutes, the roasting temperature is 1140°C, and roasting is carried out; the roasted lightweight aggregate is cooled from 1140°C to 1000°C by natural cooling; then the temperature is rapidly cooled from 1000°C to 750°C, the rapid cooling rate is 20°C / min, the temperature is kept at 750°C for 15 minutes, and the temperature is slowly cooled from 750°C to 400°C, the slow cooling rate is 5°C / min, and the temperature is rapidly cooled after 400°C, the rapid cooling rate is 20°C / min;
[0097] After the lightweight aggregate cools to room temperature, measure the water absorption, apparent density and strength.
[0098] Comparative Example 2
[0099] This comparative example provides a non-burning light aggregate, comprising the following raw materials in parts by weight: 33 parts of blast furnace slag powder, 38 parts of fly ash, 10.5 parts of expanded perlite powder, and 18.5 parts of NaOH aqueous solution, wherein the concentration of the NaOH aqueous solution is 6 mol / L;
[0100] The preparation method of the above-mentioned non-burning light aggregate comprises the following steps:
[0101] S1. Mix 33 parts by weight of blast furnace slag powder, 38 parts by weight of fly ash, and 10.5 parts by weight of expanded perlite using a mortar mixer for 5 minutes to form a uniform mixture;
[0102] S2, weigh the mixed material in S1 and add it into the disc granulator, start the granulator, and use a spray device to spray 18.5 parts by weight of NaOH aqueous solution after it runs smoothly to obtain granules with an average particle size of 2.5 mm; the disc granulator has a disc diameter of 500 mm, a depth of 45 mm, a disc inclination angle of 36°, and a rotation speed of 30 r / min;
[0103] The prepared pellets were placed in an environment at room temperature (25±3°C) and relative humidity of 65% to harden for 1 hour, then sieved, placed in sealed bags and sealed and cured at 25±3°C until the age of 28 days.
[0104] Performance Testing
[0105] The light aggregate prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was analyzed for bulk density, apparent density, water absorption, cylinder compressive strength, and pore structure, as shown in Table 1. The pore structure analysis was performed using a MesoMR12-060H-1 low-field nuclear magnetic spectrometer produced by Suzhou Newmai Company. The instrument had a constant magnetic field strength of 0.5±0.05T, a main frequency of 21.3MHz, and a coil size of 25mm, and the pore structure distribution data of 0.0001 to 1000μm was obtained.
[0106] Table 1 - Properties of lightweight aggregates prepared in different embodiments
[0107]
[0108]
[0109] The pore structure data in Table 1 represent the volume percentage (%) of pores within different pore diameter ranges.
[0110] It can be seen from Table 1 that the apparent density and bulk density of the embodiment are both relatively light, and the water absorption rate can reach more than 15%, the cylinder pressure strength is more than 18MPa, and it has a good fine interconnected pore structure. Compared with Comparative Example 1, a fired light aggregate is heavy, and due to high-temperature firing, there are more large pores, fewer connected pores and no connection, so its water absorption rate is low. Compared with Comparative Example 2, a non-fired light aggregate is relatively light, with a water absorption rate of more than 13%, but because it relies solely on the hydration strengthening effect of mineral admixtures, its cylinder pressure strength is not high, only 7.8MPa, and there are not many fine connected pores, which is not conducive to production.
[0111] In summary, the carbonized steel slag light aggregate prepared by the present invention can be used as a light aggregate to partially or completely replace sand and gravel to produce ultra-high performance concrete, with a strength grade of more than 120MPa, effectively reducing the utilization rate of sand and gravel and protecting the ecological environment. It can also be used as aggregate to produce building concrete, self-repairing concrete, road concrete, etc. Large-scale consumption of carbonized steel slag can, on the one hand, improve the activity of steel slag and solve the problem of poor stability, and on the other hand, it can consume CO2, providing a new way for the comprehensive utilization of steel slag, and also providing a new idea for carbon emission reduction in the building materials industry.
[0112] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0113] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.
Claims
1. A steel slag lightweight aggregate, characterized in that: The invention comprises the following raw materials in parts by weight: 35-60 parts of steel slag powder, 15-30 parts of porous silicate powder, 8-12 parts of silicate cement, 1-5 parts of silica fume and 15-25 parts of water.
2. The carbonized steel slag lightweight aggregate according to claim 1, characterized in that: The steel slag powder includes the following components by mass fraction: CaO: 52.62% ~ 58.23%, SiO2: 29.71% ~ 36.85%, Al2O3: 2.57% ~ 5.94%, MgO: 3.47% ~ 6.68%, loss on ignition 1.72% ~ 3.16%; The steel slag powder has a particle size of 0.05 to 0.15 mm.
3. The steel slag lightweight aggregate according to claim 1, characterized in that: The porous silicate powder is diatomaceous earth powder, and the mass content of SiO2 in the diatomaceous earth powder is greater than or equal to 88.95%; the average pore size of the diatomaceous earth powder is 56-57nm, the particle size is ≤0.075mm, and the ignition loss is 0.35-0.45%.
4. The steel slag lightweight aggregate according to claim 1, characterized in that: The silicate cement is silicate cement with a strength grade of 52.
5.
5. The steel slag lightweight aggregate according to claim 1, characterized in that: The specific surface area of the silica fume is 24 to 26 m 2 / g, loss on ignition ≤5.0%.
6. A method for preparing steel slag lightweight aggregate according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, modifying the porous silicate powder with a modifier, and crushing the modified porous silicate powder to obtain a modified porous silicate powder; S2, mixing steel slag powder, modified porous silicate powder, silicate cement and silica fume to obtain a mixture; S3, adding water to the mixture, granulating, and obtaining light aggregate; S4. Put the light aggregate into a carbonizing kettle for carbonation curing, and then perform standard curing to obtain carbonized steel slag light aggregate.
7. The method for preparing steel slag lightweight aggregate according to claim 6, characterized in that: After mixing the modifier with the porous silicate powder, water is added and the mixture is continuously mixed to obtain a mixture; The mixture is placed in a calcining furnace and heated from room temperature to 800-1100°C within 3-4 hours, and kept warm for 1.5-2 hours. The modified mixture is then crushed to a particle size of ≤0.075 mm to obtain modified porous silicate powder.
8. The method for preparing steel slag lightweight aggregate according to claim 7, characterized in that: The modifier is Na2CO3, and the mass of the modifier is 5-10% of the mass of the porous silicate powder. After the modifier and the porous silicate powder are mixed, in the step of adding water, the mass of the water is 0-15% of the mass of the porous silicate powder.
9. The method for preparing steel slag lightweight aggregate according to claim 6, characterized in that: During granulation, the granulator has a granulation angle of 40 to 60° and a rotation speed of 30 to 40 r / min; The particle size of light aggregate is 0.1~4.75mm.
10. The method for preparing steel slag lightweight aggregate according to claim 6, characterized in that: The process parameters of carbonation curing control are: carbonization temperature is 20-24℃, relative humidity is 50%-70%, carbonization carbon dioxide pressure is 0.1-0.5MPa, and carbonization time is 4-48h; The process parameters for standard curing control are: curing temperature of 18-22°C, relative humidity greater than or equal to 95%, and curing time of 28 days.